2006
DOI: 10.1111/j.1478-405x.2006.00422.x
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation, Immunity, Vaccines for Helicobacter Infection

Abstract: The reason why some individuals remain Helicobacter pylori infected for life but without any symptoms while others develop severe diseases is only partially clarified. Presumably, it depends on multifactorial interactions among host immunologic and physiologic factors, bacterial virulence determinants, and environmental influences modulating the host response. Much effort has been made to identify host genetic factors that may explain an individual susceptibility of the host to H. pylori infection. The identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 57 publications
1
25
0
1
Order By: Relevance
“…In vivo , such deep disruption of the epithelial barrier by H. pylori components and inflammatory mediators may facilitate damage to lamina propria, and promote the development of both local and systemic inflammatory response. H. pylori antigens penetrating across the gastric epithelium, can be processed in lamina propria by macrophages via PRR and presented to T lymphocytes[8,19,20]. However, it has been shown that H. pylori LPS is able to downregulate the lymphocyte blastogenic response, probably due to the interference with the process of macrophage maturation[46-48,94].…”
Section: Discussionmentioning
confidence: 99%
“…In vivo , such deep disruption of the epithelial barrier by H. pylori components and inflammatory mediators may facilitate damage to lamina propria, and promote the development of both local and systemic inflammatory response. H. pylori antigens penetrating across the gastric epithelium, can be processed in lamina propria by macrophages via PRR and presented to T lymphocytes[8,19,20]. However, it has been shown that H. pylori LPS is able to downregulate the lymphocyte blastogenic response, probably due to the interference with the process of macrophage maturation[46-48,94].…”
Section: Discussionmentioning
confidence: 99%
“…Since then, numerous vaccination strategies were explored ranging from whole H. pylori lysates to recombinant protein antigens in combination with adjuvants and from naked DNA, to viral vectors and live recombinant bacterial carriers. These have been extensively reviewed recently (Kabir, 2007;Chmiela and Michetti, 2006;Aebischer et al, 2005) and for the purpose of this review it suffices to recall that most of these approaches showed similar efficacy in animal models, i.e., lowering bacterial burden by approximately two orders of magnitude. Our own efforts focused on a vaccine design based on the licensed, live typhoid fever vaccine Metzger et al, 2004) Ty21a -a chemically induced avirulent mutant of Salmonella enterica serovar Typhi -because of its ability to induce broad cellular and humoral immunity at mucosal sites.…”
Section: Introductionmentioning
confidence: 98%
“…The course of H. pylori infection depends on the effectiveness of the host immune responses against this pathogen, both innate (unspecific) and adaptive (specific). During H. pylori infections, the dense infiltration of the gastric mucosa with immunocompetent cells indicates that the complex interactions between bacterial and host immune cells may be important for both gastric pathologies and the efficiency of pathogen elimination (3). Th1 effector lymphocytes dominate in H. pylori infected gastric mucosa (4–6).…”
mentioning
confidence: 99%